Job scheduling strategies for parallel processing : 22nd International Workshop, JSSPP 2018, Vancouver, BC, Canada, May 25, 2018, Revised selected papers /: 22nd International Workshop, JSSPP 2018, Vancouver, BC, Canada, May 25, 2018, Revised selected papers. (2019) - Unknown
No abstract available